2012
DOI: 10.1080/07448481.2011.589419
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe Smoking Among College Students in the United States: A Review of the Literature

Abstract: Despite its harmful health effects, waterpipe smoking is quite common among college students. Future research with better methodologies and theoretical frameworks are needed to advance the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
5
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 35 publications
7
100
5
3
Order By: Relevance
“…22,25,28,35,[44][45][46][47][48] However, although another study 49 found religiosity to be a protective factor against use, in this study this association lost significance after we controlled for other demographic, socioeconomic, and substance use variables. Although still rudimentary, the socioeconomic dynamics of hookah use are gradually x 2 s are design-based to account for the complex sampling design.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…22,25,28,35,[44][45][46][47][48] However, although another study 49 found religiosity to be a protective factor against use, in this study this association lost significance after we controlled for other demographic, socioeconomic, and substance use variables. Although still rudimentary, the socioeconomic dynamics of hookah use are gradually x 2 s are design-based to account for the complex sampling design.…”
Section: Discussioncontrasting
confidence: 66%
“…13 Individual studies have linked use to esophageal cancer, 14,15 chromosomal aberrations, 16 decreased pulmonary and cardiovascular functions, 17,18 infertility, 19 dental problems, 20 and infectious diseases. 21 Surveys of university students in multiple countries, including the United States, suggest that people are unaware of these dangers [22][23][24][25][26][27][28][29][30][31][32][33][34][35] and believe that hookah is less harmful and less addictive than cigarettes. 22,23,[25][26][27][28][29][30][31][32][33][34][35] A number of studies have examined the prevalence and correlates of hookah use among local and national populations, 9,36 including US adolescents.…”
mentioning
confidence: 99%
“…Seit einigen Jahren gibt es auch in vielen westlichen Ländern Hinweise auf eine zunehmende Verbreitung des Wasserpfeifenkonsums, insbesondere bei Jugendlichen und jungen Erwachsenen [4][5][6][7][8]. In den USA ist diese Entwicklung empirisch bereits gut dokumentiert [9][10][11][12][13][14][15]. Im Jahr 2007 warnte die American Lung Association eindrück-lich vor den gesundheitlichen Folgen dieses Trends [16].…”
Section: Hintergrundunclassified
“…Zwar ist Jugendlichen unter 18 Jahren durch die Novellierung des Jugendschutzgesetzes ( § 10) seit dem 1. September 2007 der Zugang zu Gaststätten, in denen geraucht wird, prinzipiell untersagt und die Abgabe von Tabakwaren an Minderjährige verboten [55], allerdings werden Wasserpfeifen, -tabak und -zubehör auch über das Internet angeboten und stark beworben [11,57,58]. Aus Public-Health-Sicht birgt diese Entwicklung ein großes Risiko, zumal die Gesundheits-und Suchtgefahren des Wasserpfeifenkonsums noch immer von einem Großteil der Jugendlichen systematisch unterschätzt werden [1,37,59].…”
unclassified
“…Prior reviews of the hookah smoking literature on college students have focused on epidemiology, specific subpopulations -particularly youths and college students (34), global health impact (35), health risks (8,28), and policy (36,37). This literature review examines hookah tobacco smoking within the context of the current mandate of the U.S. Food and Drug Administration (FDA) to regulate tobacco consumption.…”
Section: Introductionmentioning
confidence: 99%